Adaptive Pathways of Microorganisms to Cope With the Shift From P- to N-Limitation in Subtropical Plantations - Wang, Chaoqun; Jiao, Ruzhen (Frontiers in Microbiology, 2022)
Ecological stoichiometry is increasingly acknowledged as one of the main control factors for microbial activity and diversity. The soil carbon:nitrogen (C:N) and carbon:phosphorus (C:P) ratios are usually much higher than microbial nutrient requirements and vary with planting density and stand age in forestlands. However, how microorganisms cope with such stoichiometric imbalances and how they regulate nutrient cycling remain unclear. Here, 5- and 35-year-old experimental Cunninghamia lanceolata [Lamb.] Hook plantations with five planting densities (1667, 3333, 5000, 6667, and 10000 stems ha–1) were used to explore the underlying mechanisms of the response of microorganisms to stoichiometric imbalances. We found that (i) enzyme activity and microbial biomass and diversity increased with planting density at age 5 but decreased at age 35; (ii) soil microorganisms were P limited at age 5, while gradually shifted from P- to N-limitation during the development of plantations from 5 to 35 years; (iii) significantly negative relationships between microbial biomass stoichiometry and enzymatic stoichiometry were observed. The adaptive pathways of soil microorganisms to cope with stoichiometric imbalances include (i) adjusting the stoichiometry of microorganisms and enzymes; (ii) changing the relative abundance of the dominant microbial phyla; and (iii) increasing the ratio of fungal to bacterial diversity. These results highlight how to use the ecological stoichiometry method to identify soil microbial nutrient limitation with planting density during the development of plantations. By underlining the important role of stoichiometry on microbial growth and activity, these findings furthermore emphasize the dependency of organic matter transformation and nutrient cycling on the microbial community.